(untitled) (Innovative professional education, 2025)
The article is devoted to the pressing issue of implementing digital technologies in the education sector with the aim of forming an independent, responsible, and socially active individual within its system. The features and development of digital technologies in the educational process are explored. The effectiveness of using digital technologies in education largely depends on how methodologically sound and pedagogically justified their inclusion in the structure of the educational process was. The use of digital technologies in distance learning has had a positive impact on the education of learners, as seen during the Covid-19 pandemic and now in the context of the martial law introduced in Ukraine.